2020
DOI: 10.1016/j.cub.2020.04.086
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Receptor Inhibition Is Fundamental to Odor Encoding

Abstract: Highlights d Odor mixture encoding requires extensive modulation of odorant receptor activity d A combinatorial binding logic exists for antagonists, like agonists d Widespread antagonism increases the encoding capacity of the olfactory system d Divergent antagonism among paralogs diversifies odorant receptor repertoires

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 78 publications
(101 reference statements)
1
50
0
Order By: Relevance
“…As discussed in [28], additional odor-receptor interactions such as synergy, suppression, antagonism, inhibition, etc., can readily be included in the receptor response model. The prevalence of such interaction are only beginning to be investigated on large scales [44]. If the statistics of such odor-receptor interactions are known, they can be included in our model (see below).…”
Section: Decoder Of Odor Compositionmentioning
confidence: 99%
“…As discussed in [28], additional odor-receptor interactions such as synergy, suppression, antagonism, inhibition, etc., can readily be included in the receptor response model. The prevalence of such interaction are only beginning to be investigated on large scales [44]. If the statistics of such odor-receptor interactions are known, they can be included in our model (see below).…”
Section: Decoder Of Odor Compositionmentioning
confidence: 99%
“…Contemporary studies revisiting or rediscovering this phenomenon have made broad measurements of odor and mixture effects upon OSN activation levels in the intact epithelium that reflect these pharmacological principles, illustrating that odorant receptor antagonism is a common and widespread phenomenon [37-39, 41, 42]. In particular, it has been observed that this antagonism has benefits for representing mixtures containing larger numbers of different odorants without saturation [39], as illustrated here in Figure 4. The improved "encoding capacity" that these authors suggest arises from antagonism, however, would not arise from sparseness -which is not directly relevant here -but for the reasons outlined in Effects of different receptor efficacy Gaussian functions and illustrated in Figure 4.…”
Section: The Diversity Of Pharmacological Interactionsmentioning
confidence: 93%
“…Notably, we found that the highest absolute discrimination sensitivities were attained with narrower efficacy Gaussians -that is, ligand-receptor interactions with relatively high likelihoods of competitive antagonism ( Figure 4C, left panel). Primary olfactory receptors, like any receptor, certainly have weak and antagonist ligands [32,33,[37][38][39][41][42][43][44], though the probabilities of each of these different ligand-receptor interactions for any given receptor complement clearly depend on the statistics of the odor environment in which it is deployed. In the present simulations, the maximum peak discrimination sensitivity was observed when the efficacy standard deviations were roughly 0.10 q-units ( Figure 4C).…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the precise pathway(s) involved in the homogeneous perception of odor mixtures remains poorly understood [6,10]. To date, they are mainly target approaches, which concern the interactions of odorants at the OR and olfactory sensory neuron levels [11][12][13][14][15][16][17][18][19][20][21][22], evoking odorants that are involved as agonists/antagonists of their biological targets.By contrast, we focused on a ligand approach, which is complementary to the target approach. In the context of aroma blending, our approach consisted of considering a set of odorants, whose selection was based on aroma blending and whose perceptual and configural characteristics have been previously carefully investigated in studies performed with animals [23,24] and humans [25][26][27].…”
Section: Introductionmentioning
confidence: 99%